Hubungan Kecerdasan Emosional dengan Prestasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti kelas XII di SMAN 13 Padang: Hubungan Kecerdasan Emosional dengan Prestasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti kelas XII di SMAN 13 Padang - Fachlul Azmi; Indah Muliati (KOLONI, 2024)
This study aims to analyze the relationship between emotional intelligence and student achievement in Islamic Education and Character Education subjects in the twelfth grade at SMAN 13 Padang. The method used is quantitative with a correlational approach, involving 80 randomly selected students. Data on emotional intelligence were measured using a validated questionnaire, while academic achievement was assessed through report card grades. Data collection techniques included observation, questionnaires, and documentation. Data analysis was conducted using SPSS version 26.0 for Windows with Pearson Product Moment statistical technique. The results of the study showed a correlation value of rxy equal to 0.371. Referring to the r-table value of the Product Moment correlation coefficient at a significance level of 5%, which is 0.220, it can be concluded that rxy is greater than r-table (0.371 ≥ 0.220). This indicates a positive correlation between emotional intelligence and student achievement. The conclusion of this study is that students with higher emotional intelligence tend to have better academic performance. These findings underscore the importance of emotional intelligence in the learning process at school.